Development and quality evaluation of apple pomace incorporated functional apple burfi - singh, Tanuja; Pathak, Vikas; Goswami, Meena (Indian Journal of Dairy Science, 2017)
The present study was carried out to evaluate the functional and nutritional properties of burfi prepared by incorporation of apple pomace at three different levels viz. 5, 10 and 15% and compared with control. The mean moisture and carbohydrate content increased in significant (p